Effects of Business Jihad on Entrepreneurs' Motivation and Performance - Zulkarnain, Kedah; Md. Aftab, Anwar; Suhaimi, Mhd Sarif; Aahad M., Osman-Gani (2017)
Despite being misinterpreted in many different ways, the concept of Jihad can be adopted to convey positive virtues in various aspects of life. While many studies have been generated on the topic of Jihad after the September 11th attack, little information is available in the area of business Jihad. The purpose of this study is to explore the effects of business Jihad on entrepreneurs'motivation and performance. Nine experienced and successful Muslim entrepreneurs were selected to participate in this study which was conducted by using in- depth interviews. The results revealed that the adherence to the philosophy of business Jihad has significant positive impact on the entrepreneurs' motivation and performance. Therefore, these findings have the capacity to inspire the leaders from various government agencies and entrepreneurs to work together in instilling the spirit of business Jihad as a means to achieve high motivation and performance in the business world.